Desain Media Berbasis Protokol Kesehatan Covid-19 - Nadia Diandra; Mulyadi Sugih Dharsono; Van Basten (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The Covid-19 pandemic has changes the world. The Covid-19 disease, which initially had an impact on human health, is now having a global economic impact. The construction industry is one of the industries that is affect the economic impact of the ongoing Covid-19 pandemic. Several regions in Indonesia have implemented a new normal by implementing 5M which aims to reduce the number of positive cases exposed to the virus. This community service activity is carried out by socializing health protocols and planning health protocol-based media design activities for housing cluster construction projects. The hope of Community Service Activities is to increasing the awareness of project workers in implementing the Health protocol by implementing the 5M, namely washing hands, wearing masks, maintaining distance, staying away from crowds and limiting mobility. Media based on health protocols are needed and created to facilitate workers who come from outside the area, so that they can protect workers and the community who are in the area and can reduce the spread of Covid-19.